Assessment of Memory among Traumatic Brain Injury Patients during Follow-Up at a Tertiary Health Care Facility in Rural Setting - Singh, Anamika; Kumar, Raj; Ansari, Ahmad; Singh, Naresh Pal; Singh, Amit Kant (Indian Journal of Neurosurgery, 2021)
Background Head injury is an important public health problem nowadays. Traumatic brain injury (TBI) results from external force that leads to damage to brain tissue. Main causes of TBI are motor vehicle collisions and fall from height. One of the primary symptoms after TBI is impaired word retrieval. Therefore, this study was undertaken to assess memory impairment in TBI patients following treatment to asses a residual memory status to declare them apt for official works if improved enough.Objectives The purpose of this study was to assess memory impairment in TBI patients to assess the residual memory status following treatment.Materials and Methods The study was conducted in Outpatient Department (OPD) of Neurosurgery, Uttar Pradesh University of Medical Sciences, Saifai, Etawah, Uttar Pradesh. The TBI patients were assessed by predesigned memory assessment questionnaire during their follow-up following discharge from hospital.Results A total of 65 patients with TBI were assessed, of which 21 (32.3%) cases had frontal lobe injuries with 9 of 21 having memory loss (42.9% cases). The temporoparietal lobe was affected in 10 (15.4%) cases out of which 5 developed memory loss, that is, 50% cases. The multiple lobes were involved in 24 (36.9%) cases, out of which memory impairment occurred in 9 cases, that is, 37.5%. Four of total five cases (80%) of diffuse axonal injury had memory loss. Further, 16.9% (n = 11) TBI patients were unable to perform digit span test (immediate memory test), 44.6% (n = 29) cases could not perform three-word recall at 5 minutes (short-term memory test), and 15.4% (n = 10) cases could not perform (long-term memory test).Conclusion The study showed that memory assessment is required in TBI patients for instituting proper rehabilitation measures and to allow them for sensitive memory-related work following discharge from hospital.
Keywords: traumatic brain injury; memory impairment